REDESAIN BENDUNG KEDUNG JERUK KECAMATAN PRINGAPUS KABUPATEN SEMARANG - Paryanto Paryanto; Wibisono Handoko Putro; Totok Apriyanto; Ratih Pujiastuti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Water is one an important element that can affect life in nature. To increase water resources, a long-term and short-term strategy is needed. Kelampok River has not been utilized optimally by the community. For this reason, it is necessary to build a weir that serves to raise water level. The planning for the construction of the Kedung Jeruk Weir in Pringapus District, Semarang Regency aims to improve the socio-economic environment in the surrounding area.The redesign is based on secondary data with other supporting data. The analyzes carried out include: hydrological analysis, planning dimensional, analysis of the stability of the weir body, and the safety of the weir body.From the results of the hydrological analysis which includes the calculation of planned rainfall using the Thiesen Polygon method and flood discharge using the Synthetic Unit Hydrograph (HSS) Gama 1 method, the water requirement for irrigation in Pringapus Village is 0.3091 m3/s and the 50th flood discharge is 206, 01 m3/s. Weir width 36 m with 0.83 m high weir. The width of the weir crest is 30.4 m, the flushing width is 3.6 m and the pillar width is 2 m (2 Pillars 1 m each). The radius of the weir of the round threshold type is 0.8 m, the stilling pool type is USBR Type III with a length of 9 m. The value of stability during normal water conditions and flood water conditions is still above the safety value so that the weir building meets the requirements and is safe.